2016
DOI: 10.1007/s10725-016-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

Brassica napus Cycling Dof Factor1 (BnCDF1) is involved in flowering time and freezing tolerance

Abstract: DNA binding with One Finger (DOF) transcription factor plays important roles in many aspects of plant growth and development, but the molecular mechanisms behinds its actions in plant development and stress tolerance are little known. Here, we report on the Brassica napus DOF gene, which is homologous to Arabidopsis Cycling DOF Factor1 and functions as a transcriptional regulator with regard to flowering time and freezing tolerance. The BnCDF1 gene was ubiquitously expressed in plants, and its expression was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…The CO gene is involved in regulating flowering under long days, and its repression by CDF1 represses flowering in Arabidopsis [ 44 , 73 ]. Its ortholog in B. napus , BnCDF1 ( BnaDof54 in our study), was also reported to play a role in flowering [ 74 ]. BnaDof54 , functionally annotated to be involved in flower development, shows very high expression in flowers.…”
Section: Discussionmentioning
confidence: 94%
“…The CO gene is involved in regulating flowering under long days, and its repression by CDF1 represses flowering in Arabidopsis [ 44 , 73 ]. Its ortholog in B. napus , BnCDF1 ( BnaDof54 in our study), was also reported to play a role in flowering [ 74 ]. BnaDof54 , functionally annotated to be involved in flower development, shows very high expression in flowers.…”
Section: Discussionmentioning
confidence: 94%
“…PpDof1 serves as transcriptional repressor and is involved in the growth of nutrient-dependent filament in Physcomitrella patens [24]. BnCDF1 , a member of Dof family TF, takes part in regulating the flowering time and freezing tolerance in Brassica napus [25]. Overexpression of PpDof5 gene from maritime pine in transgenic Arabidopsis enhances the content of lignin [26].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressing SlCDF1 or SlCDF3 in Arabidopsis showed increased drought and salt tolerance 41 . In Brassica, the BnCDF1 gene was induced in response to low temperatures, and overexpressing BnCDF1 in Arabidopsis could increase freezing tolerance 42 . In watermelon, nine selected Dof genes showed differential expression under salt stress and ABA treatments 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we postulate that SoDof22, SoDof3 and SoDof15 have an important role in responding to heat, cold and drought stresses. Notably, overexpressing BnCDF1 in Arabidopsis also delays owering time by reducing the expression of CO and FT 42 . Interestingly, SoDof22 contains high expression level both in in orescence and under cold stress, suggesting that the role of SoDof22 might be similar to BnCDF1 within the interplay between environmental conditions and owering time.…”
Section: Discussionmentioning
confidence: 99%